Affidavit [On the Recognition of Cree Hunting Territories Outside the James Bay Territory, 1975 - 1984] - Feit, Harvey A. (My University, 2008)
This Affidavit was prepared at the request of the Cree Nation of Mistissini for their court case against the Government of Canada’s failure to recognize Cree rights on lands that fall outside the eastern boundary of the territory covered by the James Bay and Northern Québec Agreement of 1975 (JBNQA). I presented evidence that the Government had committed to recognition of these lands, and that it had recognized them in practice during and after the negotiation of the JBNQA. The first part of my Affidavit presented a social scientists’ view of the importance of hunting territories as forms of Cree governance, and as central to the families, societies and economies of James Bay Crees. It also indicated that Cree hunting territories, Indoh-hoh Istchee, were a non-cadastral system of tenure and governance, and a part of mixed systems of conservation and co-governance. It documented how Cree hunting territories outside the JBNQA territory were acknowledged during the negotiation of the JBNQA and were given some recognition within it. The Affidavit documented how it was agreed by governments and Cree that the continuity of Cree land usage, and the mobility of wildlife, meant that managing and conserving wildlife and the environment required that all lands the Cree used be treated together and under the same regimes. As a participant, an ethnographer and an academic, I traced and recalled discussions through drafts of the Agreement sections on hunting, and minutes and position papers, and documented how the need to recognize Cree lands outside the JBNQA territory was repeatedly acknowledged by representatives of Indigenous Peoples and governments in 1975. When there was no agreement by all negotiators to include recognition of these lands in the legal text of the Agreement, for legal consistency, there was an understanding that these legal issues would be addressed later outside the JBNQA. I then showed how various research and management activities under the JBNQA, both before and after its signing, did of necessity deal with all Cree lands and in the same way. They also often explicitly acknowledged the anomalies of the JBNQA legal situation vis-a-vis these lands outside the JBNQA territory. This extended not only to scientific and administrative personnel, recognition also occurred in negotiations of accords required under and subsequent to the JBNQA where negotiations were conducted by government appointees mandated to act in the name of the respective governments not just to represent and report back to ministers. The Affidavit concluded: “This series of decisions, implementation actions, and negotiations, each taken in unanimity by negotiators or representatives of the Aboriginal and government parties, were consistent throughout the decade [1975-84]. They acknowledged that Cree Indoh-hoh Istchee - traplines or hunting lands extended beyond the eastern boundary of the 1898 - 1912 [JBNQA] territory, and that the general principles and guarantees of Section 24 of the JBNQA applied to these lands the same as they did to Indoh-hoh Istchee within the 1898 -1912 [JBNQA] territory. It was also agreed that unresolved issues concerning Cree Indoh-hoh Istchee - traplines or hunting lands outside the 1898 - 1912 territory required additional measures.”
It should be noted that Crees did not seek to change the boundaries of the lands under consideration in the court case against the hydroelectric project to better coincide with Cree land limits. This would not have been advantageous to the Cree for reasons related to the distinct legal status of these lands in Canadian law. The territorial boundaries of the 1972 court action were embedded in laws going back to 1898 and 1912, laws that created legal anomalies among the rights of state governance jurisdictions. The ambiguities relating to the status of these lands strengthened the legal arguments of the Crees as they tried to stop the ongoing hydroelectric project. In 2008, after my Affidavit was submitted, a decision was taken by some Cree authorities not to pursue this case to a ruling.
Keywords: Indigenous Rights; Messy Co-governance; Law and Governance Anomalies; Negotiating Land Claims Agreements; Treaty Commitments Broken; Hunting Territories; Mistissini Cree; James Bay Cree; James Bay and Northern Quebec Agreement (JBNQA)